2022
DOI: 10.2147/jir.s365090
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effect of Azilsartan Through Ameliorating Oxidative Stress, Inflammation, and Restoring Hydroxyproline, and Gastrin Levels in Ethanol-Induced Gastric Ulcer

Abstract: Objective The present study was designed to evaluate the possible gastroprotective effects of different doses of azilsartan in ethanol-induced gastric ulcers in rats. Methodology Forty-eight male adult Wistar rats were used and allocated randomly into four groups: negative control treated with distilled water, positive control treated with ethanol, lansoprazole treated group, and azilsartan (1mg, 5mg, and 10mg/kg) treated group. The treatment protocol was for 15 days, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…We found a significantly increased serum gastrin level and gastric acid production, confirmed by low gastric pH in the ulcer group. These results concurred with recent studies [ 40 , 51 ]. The pantoprazole group showed a significantly increased serum gastrin level in comparison with the ulcer group.…”
Section: Discussionsupporting
confidence: 94%
“…We found a significantly increased serum gastrin level and gastric acid production, confirmed by low gastric pH in the ulcer group. These results concurred with recent studies [ 40 , 51 ]. The pantoprazole group showed a significantly increased serum gastrin level in comparison with the ulcer group.…”
Section: Discussionsupporting
confidence: 94%
“…However, treatment with Azil reduced MDA level in striatum of 3-NP-treated rats, demonstrating its anti-oxidant properties that could contribute to its neuroprotective potential. Azil was previously reported to ameliorate oxidative stress in ethanol-induced gastric ulcers in rats [ 82 ] and cerebral ischemia reperfusion at model [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, previous investigations revealed the gastroprotective roles of medicinal plants and their natural products and they have been linked with the plant's phytochemical potentials in the positive modulation of various physiological processes ( Hama Amin and Aziz, 2022 , Ibrahim et al, 2016 ). Moreover, the current study revealed lower ulcer area (index) and total ulcer score in REPP-treated groups were very comparable to reference groups (omeprazole).…”
Section: Discussionmentioning
confidence: 99%